Development of yeast expression systems for producing thermostable T1 lipase - Oslan, Siti Nurbaya (2012)
Escherichia coli is known to be a good system to express heterologous protein. However, proteins always form as inclusion bodies and low level of active protein could be achieved through this system. In addition, the proteins were expressed intracellularly, thus required tedious purification steps. In order to overcome the problems, yeast expression system was developed. This study highlights on the development of yeast expression systems to express thermostable T1 lipase from Geobacillus zalihae. This study has three chapters which cover on isolation of local yeasts, expression of T1 lipase in commercial and local yeast system. Finally, the new yeast-vector system was constructed to express the protein. Eight yeast isolates were isolated from different sources (isolate: WB, SO, S4, S5, R1, R2, RT, and RG). The isolates were identified through PCR amplification and sequencing of the ribosomal DNA. Among the isolates, isolate WB was determined as new species in order Saccharomycetales. Isolate SO, RT and RG were identified as Pichia sp. While isolates S4 and S5 were determined as Issatchenkia sp. Isolates R1 and R2 were grouped in Hanseniaspora sp. Geneticin 50 μg/mL was determined to be the selection marker for all isolates except for isolates RT and SO. Some thermostable lipases were observed in isolates RT and R1 with 0.61 U/mg and 0.1 U/mg, respectively. All Pichia sp. strains possessed formaldehyde dehydrogenase (FLD) promoter. However, only isolate SO has the alcohol oxidase (AOX) promoter. Commercial yeast expression system, Pichia pastoris strains (GS115, X-33 and KM71H) was used to express T1 lipase under regulation of methanol inducible AOX promoter by using pPICZαB. Recombinants X-33/pPICZαB/T1-2 (XPB2), GS115/pPICZαB/T1-5 (GPB5) and KM71H/pPICZαB/T1-7 (KPB7) were chosen for optimization of T1 lipase expression in shake flask. 2% (v/v) methanol was used to induce GPB5 and XPB2 optimally, while 3% (v/v) methanol for KPB7. The highest expression level was attained at the optimum time with GPB5 (88 U/mL – 192 h), XPB2 (81 U/mL – 144 h) and KPB7 (26 U/mL – 144 h). Western blot analysis confirmed that the molecular mass of recombinant T1 lipase was 45 kDa without glycosylation. Initial study proved that thermostable T1 lipase was successfully expressed by using the secretory P. pastoris expression system at 2-fold higher than E.coli. Isolate SO was chosen to be used as a host for T1 lipase expression under regulation of commercial plasmid pPICZαB). Recombinant isolate SO/pPICZαB/T1-2 (SO2) was chosen for T1 lipase expression in shake flask. YPTG and YPTM media were used to grown and induce the SO2 expression. Methanol concentration of 1.5% (v/v) was shown to be the best inducer for recombinant SO2. The optimum T1 lipase expression was achieved after 30 h. The optimum T1 lipase expression in SO2 was 14 U/mL with 83% lower methanol and the time taken was 84% faster than commercial system. A new series of host-vector system was developed by using isolate WB and P. pastoris. Plasmid pUC19 was used as the backbone for the new episomal and integrated plasmids. Replicon from P. pastoris (PARS1) was used to maintain episomal form of plasmid (pTBR5ECT1) while 25S rDNA from isolate WB was used as integration site (pTBR5ECT1-25S and pTBR5ECT1-25S WB). TEF1 promoter from Saccharomyces cerevisiae and isolate WB were used to regulate the T1 lipase expression in new yeast system. In conclusion, locally isolated yeasts (isolate SO and WB) and commercial system (P. pastoris) were developed to be used to express recombinant thermostable T1 lipase from Geobacillus zalihae. Newly developed systems could be used to express other protein of interest.